Indoor air pollution from cooking: emission characteristics, exposure risks, and health implications - Yushi Gong; Junling Li; Hong Li; Jian Gao; Weigang Wang; Maofa Ge (Frontiers in Environmental Science, 2026)
Cooking is an indispensable activity in daily life and one of the major sources of indoor air pollution. Pollutants generated during cooking, including particulate matter (PM), ultrafine particles (UFPs), volatile organic compounds (VOCs), polycyclic aromatic hydrocarbons (PAHs), carbonyl compounds, black carbon (BC), and nitrogen oxides (NO x ), may pose potential health risks through inhalation exposure. In recent years, advances in monitoring technologies and health risk assessment methodologies have led to increasing attention being paid to the environmental behavior and health effects of cooking emissions. This review systematically examines the effects of different cooking methods, cooking materials, cooking fuels, and cooking environments on pollutant emission characteristics and associated human health risks. Current evidence indicates that high-temperature cooking processes, particularly deep-frying and grilling, generally generate higher levels of PM and organic pollutants. The fatty acid composition of cooking oils and the biochemical precursors present in food ingredients fundamentally determine the chemical reaction pathways and risk profiles of cooking emissions. Traditional biomass and solid fuels are associated with substantially higher pollutant emissions and health risks than cleaner energy sources such as natural gas and electricity. In addition, ventilation conditions, spatial configurations, and cooking scenarios further influence pollutant dispersion and human exposure levels. Existing studies suggest that long-term exposure to cooking emissions may induce oxidative stress, inflammatory responses, and genotoxic effects, and is associated with increased risks of respiratory diseases, cardiovascular diseases, and cancer. Based on the available evidence, this review proposes a series of evidence-based recommendations and practical mitigation measures aimed at reducing exposure risks and promoting healthier cooking practices. Finally, the major findings are summarized, current research limitations are identified, and future directions for the development of safer cooking technologies and public health policies are discussed.